2018
DOI: 10.3389/fmicb.2018.00614
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Streptococcus gallolyticus subsp. gallolyticus Association With Colorectal Cancer

Abstract: Streptococcus gallolyticus subsp. gallolyticus Sgg (formerly known as S. bovis type I) is the main causative agent of septicemia and infective endocarditis (IE) in elderly and immunocompromised persons. It belongs to the few opportunistic bacteria, which have been strongly associated to colorectal cancer (CRC). A literature survey covering a period of 40 years (1970–2010) revealed that 65% of patients diagnosed with an invasive Sgg infection had a concomitant colorectal neoplasia. Sgg is associated mainly with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
98
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(102 citation statements)
references
References 81 publications
(117 reference statements)
1
98
0
3
Order By: Relevance
“…Some of the tumour genera of (possible) oral origin identi ed in our study, were associated with tumour mucosa previously, namely Fusobacterium, Campylobacter, Leptotrichia, Parvimonas, Gemella, Granulicatella, Eikenella, Selenomonas, Neisseria, Streptococcus, Alloprevotella, Veilonella, Haemophilus [8,31,32,[61][62][63][64][65][66][67][68]. In contrast, Solobacterium was reported increased [31], while Slackia and Pseudomonas were shown to be decreased [12,19] in fecal samples of CRC patients compared to healthy donors, and, in one epidemiological study, the presence of Treponema in the oral cavity was associated with increased risk of CRC [29], but none of these were previously associated with tumour mucosa.…”
Section: Tumour Crc Microbial Subtypessupporting
confidence: 57%
“…Some of the tumour genera of (possible) oral origin identi ed in our study, were associated with tumour mucosa previously, namely Fusobacterium, Campylobacter, Leptotrichia, Parvimonas, Gemella, Granulicatella, Eikenella, Selenomonas, Neisseria, Streptococcus, Alloprevotella, Veilonella, Haemophilus [8,31,32,[61][62][63][64][65][66][67][68]. In contrast, Solobacterium was reported increased [31], while Slackia and Pseudomonas were shown to be decreased [12,19] in fecal samples of CRC patients compared to healthy donors, and, in one epidemiological study, the presence of Treponema in the oral cavity was associated with increased risk of CRC [29], but none of these were previously associated with tumour mucosa.…”
Section: Tumour Crc Microbial Subtypessupporting
confidence: 57%
“…Whether Sgg is a passenger or a driver bacterium has not been completely elucidated, but is just beginning to become clear. Pasquereau-Kotula described a two-hypothesis model, by which Sgg either contributes to CRC development as a consequence of local microbial imbalance or actively accelerates transformation due to high colonization in pre-malignant epithelium along with specific inflammatory responses and increased cell proliferation 46 . Growing evidence supports the former with Sgg not being a bona fide pathogen, but likely benefits www.nature.com/scientificreports www.nature.com/scientificreports/ from the microenvironment created by preneoplastic glands in the gut 9 .…”
Section: Discussionmentioning
confidence: 99%
“…The nature and the etiological role of S. gallolyticus with colon neoplasm have been extensively studied in mice. It is suggested that S. gallolyticus might be passengers and cancer-promoting bacteria [11]. The underlying mechanisms remain to be clarified further.…”
Section: Discussionmentioning
confidence: 99%